2022
DOI: 10.3389/fcomm.2021.760847
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Persuasion: Examining the Influence of Political Ideology on COVID-19 Vaccine Uptake Hesitancy

Abstract: The COVID-19 pandemic has contributed to the death of over 625,000 Americans and it continues to have monumental consequences worldwide for economic, social and individual life. An effective vaccine program is considered vital to securing collective immunity; yet, many Americans are still hesitant to be vaccinated. This two-part study first experimentally tests two message frames (inoculation vs control) designed to counter resistance to the COVID-19 vaccine with individuals who are initially supportive, neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As a consequence, interventionists may consider using messages that highlight the utility and benefits of getting the COVID‐19 vaccine booster, consistent with intervention research adopting behavior change techniques targeting attitude change (Hamilton & Johnson, 2020 ), as well as emphasizing the importance of significant others as advocates of getting a booster vaccine, consistent with studies adopting techniques targeting normative belief change (Hagger, Cameron, et al, 2020 ; Sheeran et al, 2016 ). Such an approach may also be more effective than attempts targeting change in stable, generalized beliefs, such as vaccine hesitancy, because it may minimize psychological reactance to challenges to entrenched, strongly valued beliefs (Brinson, 2022 ). However, given the study design we are loathe to make specific recommendations for intervention, as current data do not imply causal effects or model change in intentions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, interventionists may consider using messages that highlight the utility and benefits of getting the COVID‐19 vaccine booster, consistent with intervention research adopting behavior change techniques targeting attitude change (Hamilton & Johnson, 2020 ), as well as emphasizing the importance of significant others as advocates of getting a booster vaccine, consistent with studies adopting techniques targeting normative belief change (Hagger, Cameron, et al, 2020 ; Sheeran et al, 2016 ). Such an approach may also be more effective than attempts targeting change in stable, generalized beliefs, such as vaccine hesitancy, because it may minimize psychological reactance to challenges to entrenched, strongly valued beliefs (Brinson, 2022 ). However, given the study design we are loathe to make specific recommendations for intervention, as current data do not imply causal effects or model change in intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that individuals with more conservative, right‐leaning political views are more likely to cite skepticism over COVID‐19 vaccines and less likely to state positive vaccination intentions and get vaccinated (e.g. Bilewicz & Soral, 2021 ; Brinson, 2022 ). Consistent with this prior research, political ideology would be expected to impact individuals' intentions to receive a booster vaccine, such that individuals with more conservative orientation would be less likely to intend to get a booster vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Major misinformation themes included health (k=15) and climate change (k=7), the mean participant age distribution was 18 to 48 years, and most studies were conducted in the United States (k=28). A total of 31 studies reported misinformation credibility assessment [ 7 , 13 , 14 , 16 , 22 - 24 , 26 - 28 , 39 - 48 ], 26 reported real information credibility assessment [ 1 , 7 , 14 - 16 , 22 - 24 , 27 , 41 - 43 , 49 - 54 ], 12 reported credibility discernment [ 7 , 23 , 24 , 27 , 41 ], 12 reported misinformation sharing intention [ 7 , 13 , 23 , 40 , 45 , 50 ], 11 reported real information sharing intention [ 7 , 23 , 51 , 55 ], and 8 studies reported sharing discernment [ 7 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot for the effects of psychological inoculation on real information sharing intention (k=11). Different studies in the same article are distinguished by an underscore and the numbers 1 to 6 [ 7 , 23 , 51 , 55 ]. SMD: standardized mean difference.…”
Section: Resultsmentioning
confidence: 99%
“…Vaccine perceptions and behaviors have been intricately linked to American politics, making it a complex issue that moves beyond simple public health concerns (Baumgaertner et al , 2018). Research has found that ideological identification predicted COVID-19 vaccination in the USA (Brinson, 2022). For instance, in the first year of the pandemic, 52% of Democrats reported being willing to get the COVID-19 vaccines versus 26% of Republicans who were willing (SteelFisher et al , 2021).…”
Section: Challenges To Changing Vaccine-hesitant Consumers’ Behaviormentioning
confidence: 99%